A retrospective study of state aid control in the German broadband market - Tomaso Duso; Mattia Nardotto; Jo Seldeslachts (Deutsches Institut für Wirtschaftsforschung (DIW), 2024)
We provide an evaluation of the impact of German public subsidy schemes in municipalities of Bavaria and Lower Saxony aimed at supporting the deployment of basic broadband infrastructure in rural Germany. Such subsidies are subject to state aid control by the European Commission and may only be granted if the potential market failure is addressed without distorting competition. We first analyse the consequences of the subsidies on reducing the digital divide between urban and rural areas. Second, and more novel, we examine the impact on different measures of competition: market entry and the resulting effect on prices and broadband offerings. We use an instrumental variables (IV) approach based on the interaction between technical features of the programme and political cycles in order to exploit plausibly exogenous variation in the allocation of subsidies. We find that the subsidies significantly increased broadband coverage. More interestingly, the number of internet service providers (ISPs) increased significantly in municipalities that received subsidies, which, in turn, led to a relative increase in the number of local broadband plans and a relative decrease in average prices. Our results show that well-designed state aid need not distort competition and can even enhance it.
Keywords: C23; D22; L1; L4; L64; 330; State Aid; Ex-Post Evaluation; Broadband; Coverage; Entry; Competition; Prices